Thematic structure shift in the English translation of Indonesian complex sentences in Okky Madasari's Maryam - Anisa Intan Nurfadhilah (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2016)
oen, 1/ws.c.1